A diferenciação entre os conceitos de temperatura e sensação térmica por meio de uma manifestação metereorológica à luz da teoria dos campos conceituais : uma investigação em uma escola do campo - Oliva, Izalina de Vargas (2020)
This dissertation sought to reflect on the possibilities of using technology in science teaching, as well as its contributions in the school context. An educational product was proposed and built that sought to address the differentiation between the concepts of temperature and thermal sensation. The didactic implementation took place in a regular classroom in the ninth grade of Elementary School at the Municipal Rural Elementary School Sucession dos Moraes, in the city of Dom Pedrito. The technology of the Arduino prototyping platform and block programming (Ardublock application) were used for the automation of a meteorological mini station, aimed at enhancing the teaching and learning process of the involved physics concepts. One of the objectives was to demystify the erroneous idea that the physical phenomena studied at school do not have practical connections in the students' daily life, as well as to answer questions such as: Can Physics Teaching be taught in a contextualized way in elementary school? How to use technology to promote scientific knowledge? Can the use of the Ardublock application (as a teaching resource) promote contributions to the concepts of physics? Thinking about these questions, from the use of an automated meteorological mini-station with the Arduino board and the Ardublock application, a Conceptual Field was elaborated, according to Gérard Vergnaud Conceptual Field Theory, in order to provide students with a set of problem situations aimed at conceptualizing Temperature and Thermal Sensation. At the end of the intervention, it was possible to realize that the gap between science teaching and the reality experienced by students can be overcome as long as the teacher plans his classes seeking to give meaning, taking students to understand the world in which they live without losing scientific .